Paddington [videorecording (DVD)] - King, Paul, 1978-; Bonneville, Hugh; Hawkins, Sally, 1976-; Walters, Julie, 1950-; Kidman, Nicole, 1967-; Bond, Michael (Anchor Bay Entertainment, 2015)
A young Peruvian bear travels to London in search of a home. Finding himself lost and alone at Paddington Station, he meets the kindly Brown family, who offer him a temporary haven.